Periodization and modernity(ies) in international politics through R.B.J. Walker and Jens Bartelson - Lage, Victor Coutinho; Chamon, Paulo Henrique de Oliveira (Carta Internacional, 2015)
Critical investigations in the field of IR have connected its modes of problematization to a modern discourse on politics. In this paper, we propose to further these interrogations by investigating the role of the under-theorization of ‘periodization’ in reifying too narrow a concept of ‘modernity’ and, therefore, constraining available avenues for interrogating international politics. We proceed through a double problematization. First, we problematize the role played by periodization in the work of Jens Bartelson and Rob Walker, pointing to the pervasiveness—and yet silence over—this practice in two important moves to open space to think beyond modern political discourse. Second, we problematize periodization as a political practice that regulates past, present, and future, highlighting its double role in both reifying specific conceptions of history and the present, and in opening space for thinking about alternative timelines and modernities. We thus argue that periodization can have an important role in breaking through the temporal and historical boundaries limiting our understandings of international politics.